Application of vacuum impregnation and CO2-laser microperforations in the potential acceleration of the pork marinating process. (December 2020) - Figueroa, Consuelo; Ramírez, Cristian; Núñez, Helena; Jaques, Aldonza; Simpson, Ricardo
Abstract: The marination of meat takes many hours to attain the required salt content. Vacuum impregnation (VI) and CO2 -laser microperforation have been studied to accelerate the mass transfer process and show promising results. The objective of this study was to investigate the feasibility of reducing the pork marinating time by coupling CO2 -laser microperforation and VI processes and mathematically with Fick's second law and anomalous diffusion models. Pork cylinders were microperforated and marinated with a solution containing NaCl (8% w/w) and Na5 P3 O10 (0.3% w/w) at 6 °C for 60 h. The marinating process was modeled using Fick's second law and anomalous diffusion models. The marinating process coupling VI and microperforations significantly accelerated the mass transfer compared with that of the conventional salting process, reducing the marinating processing time by 47.8%. The anomalous diffusion model was better at representing and adjusting the experimental data compared than the model based on Fick's second law. Industrial application: The marinating of meat is a process commonly applied in the meat industry, which focuses on enhancing the flavor, tenderness and juiciness of meat. However, it is a time-consuming process. Laser microperforation is a pretreatment performed on the meat in which the laser acts as a drill, creating micropores in the meat, which coupled with vacuum impregnation can be applied to accelerate the marinating process of pork meat. Applying both technologies, it is possible to reduce the processing time by almost 48%, which can relevantly and significantly increase plant productivity. Graphical abstract: Unlabelled Image Highlights: Vacuum impregnation coupled with laser microperforation reduced the processing time. Microperforated-treated pork samples followed an anomalous diffusion behavior. Vacuum impregnation-treated samples followed a Fick's second law mathematical model. Both vacuum impregnation and laser microperforations increased water retention.